Perlindungan Hukum Terhadap Anak Yang Menjadi Korban Tindak Pidana Pencabulan - Polnaya, Marselio F. H.; Supusepa, Reimon; Tuhumury, Carolina (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: The criminal act of molestation of children is a crime that violates morality, immorality and religion.Purposes of the Research: analyze the form of legal protection for children who are victims of criminal acts of obscenity, and to be able to find out the efforts to deal with children who are victims of criminal acts of obscenity.Methods of the Research: victims of sexual abuse. The type of research used is "Normative Juridical" research, and is descriptive analysis in nature, the research approach uses a statutory approach, a case approach, and a conceptual approach. The technique of collecting legal materials through library research, then analyzing the legal materials used is qualitativeResults of the Research: The implementation of child protection in the form of state responsibility is that the responsibility of the state for the promotion of children's rights is not just a legal responsibility, but a constitutional responsibility and human rights that have been recognized internationally. So it is every member of the community who seeks to protect children according to their abilities with various kinds of efforts in certain situations and conditions. Every citizen is also responsible for implementing child protection for the sake of child welfare, because child protection has a positive influence on parents, family, society, government and the state. Coordination of collaborative child protection activities needs to be carried out in order to prevent an imbalance in overall child protection activities. Efforts to deal with criminal acts of sexual abuse of minors can be carried out in two ways, namely prevention and management if criminal acts of sexual abuse of children have already occurred